Stable DNA unwinding, not "breathing," accounts for single-strand-specific nuclease hypersensitivity of specific A+T-rich sequences. - Kowalski, D (1988)
A long A+T-rich sequence in supercoiled pBR322 DNA is hypersensitive to single-strand-specific nucleases at 37 degrees C but not at reduced temperature. The basis for the nuclease hypersensitivity is stable DNA unwinding as revealed by (i) the same temperature dependence for hypersensitivity and for stable unwinding of plasmid topoisomers after two-dimensional gel electrophoresis, (ii) preferential nuclease digestion of stably unwound topoisomers, and (iii) quantitative nicking of stably unwound topoisomers in the A+T-rich region. Nuclease hypersensitivity of A+T-rich sequences is hierarchical, and either deletion of the primary site or a sufficient increase in the free energy of supercoiling leads to enhanced nicking at an alternative A+T-rich site. The hierarchy of nuclease hypersensitivity reflects a hierarchy in the free energy required for unwinding naturally occurring sequences in supercoiled DNA. This finding, along with the known hypersensitivity of replication origins and transcriptional regulatory regions, has important implications for using single-strand-specific nucleases in DNA structure-function studies.